High sperm DNA stainability might not be an accurate predictive indicator of male fertility and assisted reproductive technology outcomes - Shen, Liyan; Zhang, Ce; Wang, Gaigai; Fu, Xu; Yang, Shenmin; Wang, Jiaxiong (Frontiers in Endocrinology, 2025)
BackgroundThe clinical need for assisted reproduction continued to increase, so did the need for predictive markers of assisted reproductive technology (ART) outcomes. Among all the markers, sperm DNA integrity was paid more and more attention in the assessment of male fertility in recent years, but its clinical value remains still in doubt.MethodsWe conducted a retrospective cohort study. Couples coming to our reproductive center were retrospectively enrolled, and semen and assisted reproductive technology parameters were assessed. Sperm DNA integrity was analyzed using a flow cytometric method. Statistics were analyzed to investigate the relationship of this on semen quality and ART outcomes.ResultsDNA fragmentation index (DFI) was affected by abstinence days and age, and was a directly correlated with sperm quality parameters (p<0.001). Meanwhile high sperm DNA stainability (HDS) showed an unexplainable negative correlation with abstinence days (p<0.05), age (p<0.001) and body mass index (p<0.01).For sperm quality parameters, HDS showed a similar relevance besides abnormal sperm head morphology (p<0.001). Embryo cleavage and implantation rates were significantly negatively related to DFI in fresh intracytoplasmic sperm injection cycles (p<0.01) while HDS showed a positive relationship with high quality embryo rate (p<0.05). For final outcomes, only the live birth rate from fresh intracytoplasmic sperm injection cycles was positively correlated with DFI which is meaningless (p<0.05).ConclusionsHDS might not be an appropriate marker for male fertility and further studies are needed to identify the efficiency of SDF in clinical practice.